Impact of date palm (Phoenix dactylifera) pollen supplementation on growth performance, carcass traits, cecal microbial composition, and blood parameters in Japanese quail (Coturnix coturnix Japonica) - Soha A. Farag; Waleed M. Dosoky; Abdelrahim A. Moussa; Mahmoud Kamal; Ahmed A. Elolimy; Mohamed M.F. El-Mekkawy; Mohamed E. Abd El-Hack; Ayman A. Swelum (Poultry Science)
This study aimed to evaluate the effects of date palm pollen (DPP) supplementation in the diet of Japanese quail on growth performance, carcass characteristics, blood biomarkers, and intestinal bacterial load. A total of 360 unsexed one-day-old Japanese quail chicks were randomly assigned to four experimental groups using a completely randomized design. Each group was further subdivided into three replicates, each consisting of 30 chicks. In the experiment, the first group was given control (basal diet); the second group was given the same basal diet plus 3 g/kg of DPP; the third group was given the same basal diet plus 5 g/kg of DPP; and the fourth group was given the same basal diet plus 7 g/kg of DPP. The results revealed significant differences between treatments, with DPP supplementation leading to increased body weight (BW) and body weight gain (BWG) during the initial weeks (P < 0.05), and these differences became more pronounced (P < 0.01) in the later stages of the study. Additionally, the DPP-treated groups demonstrated lower feed intake (FI) and improved feed conversion ratio (FCR) than the control group. Supplementation with DPP significantly (P < 0.05) influenced carcass, liver, spleen, thymus, and bursa percentage. The addition of DPP to the quail diet significantly impacted (P < 0.01) all hematological parameters, except for red blood cell concentration. Biochemical analysis showed a significant increase (P < 0.01) in total protein, albumin, globulin, and high-density lipoprotein (HDL) levels in the DPP groups. In contrast, alanine aminotransferase (ALT), aspartate aminotransferase (AST), urea, creatinine, cholesterol, triglycerides, and low-density lipoprotein (LDL) levels were significantly reduced (P < 0.01). DPP supplementation had a significant impact on antioxidant enzyme activities, with the 5 g/kg and 7 g/kg DPP groups showing significant increases (P < 0.01) in total antioxidant capacity (TAC), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) levels. Furthermore, malondialdehyde (MDA) and nitric oxide (NO) concentrations were significantly reduced (P < 0.01). According to microbiological tests, the DPP-treated groups had reduced Escherichia coli and Staphylococcus aureus levels. In summary, adding DPP to the diet of Japanese quail enhances their gut microbiota composition, growth performance, carcass characteristics, and biochemical markers.